2019
DOI: 10.3390/jcm8081234
|View full text |Cite
|
Sign up to set email alerts
|

Differential Protein Expression in Human Dental Pulp: Comparison of Healthy, Inflamed, and Traumatic Pulp

Abstract: Trauma or injury to the dental pulp causes inflammation. This study compared the proteome of healthy pulp with inflamed pulp and traumatic pulp to identify the differentially expressed proteins in the diseased state. Five participants were grouped based on the pulpal status of the teeth: healthy, inflamed, or traumatic pulp. Pulp was extirpated and stored immediately in liquid nitrogen. Pulp tissues were subjected to 2-dimensional gel electrophoresis, and spot selection was performed. The selected spots were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2025
2025

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…2019); and the study of pulp and periapical pathogenesis, as well as the treatment of pulp disease (Yue et al . 2019, Loureiro et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2019); and the study of pulp and periapical pathogenesis, as well as the treatment of pulp disease (Yue et al . 2019, Loureiro et al . 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Through proteomics research in dentistry, important findings have been reported in the study of saliva (Siqueira & Dawes 2011, Lorenzo-Pouso et al 2018, acquired pellicle (Ventura et al 2017), caries (Jagr et al 2016), gingivitis (Huynh et al 2015), periodontitis (Bostanci & Bao 2017) and oral cancer (Carnielli et al 2018). In Endodontics specifically, studies are focused on three major areas: pulp regeneration and tissue engineering, based on the proteomic study of mesenchymal stem cells (Murakami et al 2012, Li et al 2017; identification of bacterial proteins from endodontic infections, mainly related to pathogenicity and microbial virulence (Provenzano et al 2013, Francisco et al 2019; and the study of pulp and periapical pathogenesis, as well as the treatment of pulp disease (Yue et al 2019, Loureiro et al 2020.…”
Section: Introductionmentioning
confidence: 99%